Amorphous nanocrystalline soft magnetic material with high saturation flux density and preparation method of amorphous nanocrystalline soft magnetic material
By compounding a small amount of insulation-coated modified spherical iron-silicon soft magnetic powder with scaly amorphous soft magnetic powder, and performing molding and annealing treatments, the existing amorphous nanocrystalline soft magnetic materials have low Bs and large high-frequency losses. problem, achieving the effects of high saturation magnetic induction intensity and low loss.
Patent Information
- Application Number
- CN202411553725.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-03
AI Technical Summary
The saturated magnetic induction strength (Bs) of existing amorphous nanocrystalline soft magnetic materials are generally low, which cannot meet the needs of high-frequency applications. Insulation coating treatment has an adverse effect on the permeability and Bs of the material.
A small amount of insulating and modified spherical iron silicon soft magnetic powder and scale -shaped non -crystal soft magnetic powder are compounded, and it is treated with molding molding and annealing. Combined with sintering processing, a highly saturated magnetic induction strength is prepared. Magnetic material.
It significantly increases the saturation magnetic induction intensity of amorphous nanocrystalline soft magnetic materials, reduces high-frequency loss, improves the bonding effect and density of the material, and improves the comprehensive magnetic properties.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to an amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity and a preparation method thereof. Background Art
[0002] Soft magnetic material is a magnetic material with low coercive force and high magnetic permeability. Soft magnetic materials are easy to magnetize and demagnetize, and are widely used in electrical and electronic equipment. Soft magnetic materials can be divided into three categories according to their composition: metal soft magnetic materials, ferrite soft magnetic materials, and amorphous nanocrystalline soft magnetic materials. The resistivity of metal soft magnetic materials is small, and the eddy current loss at high frequency is large, which means that they can only be used in medium and low frequencies of 100kHz. For this reason, the metal soft magnetic particles are surface insulated and then molded to reduce their eddy current losses and increase their operating frequency. Despite this, conventional metal soft magnetic composite materials still cannot work at higher frequencies. Ferrite soft magnetic materials have the characteristics of high magnetic permeability and high saturation magnetic induction intensity (Bs), but the loss at high frequencies is still large, which limits their application at high frequencies.
[0003] Amorphous nanocrystalline soft magnetic materials are obtained by properly annealing the amorphous precursor. The annealed phase is a composite phase composed of an amorphous matrix and a nanocrystalline precipitation phase. The precipitation of the nanocrystalline phase increases the saturation magnetic induction intensity of the material, while the exchange coupling between the nanocrystalline phases allows the material to maintain a smaller coercive force. Therefore, amorphous nanocrystalline soft magnetic materials often have better comprehensive soft magnetic properties. Generally speaking, the higher the Bs of the material, the smaller the volume and mass of the material used, which is in line with the development trend of electronic and electrical equipment towards miniaturization and high frequency. Therefore, high Bs soft magnetic materials have become a research hotspot in the field of soft magnetism.
[0004] For amorphous nanocrystalline soft magnetic materials, to increase the Bs of the material, it is necessary to increase the content of ferromagnetic elements in the material, that is, it is necessary to reduce the content of other non-ferromagnetic elements. The reduction in the content of other non-ferromagnetic elements will lead to reduced controllability of the material's crystallization process and deterioration of the material's soft magnetic properties. Therefore, in order to ensure good comprehensive performance, the Bs of amorphous nanocrystalline soft magnetic materials is generally below 1.6T.
[0005] Patent CN 111081466 A discloses a method for preparing an amorphous nanocrystalline soft magnetic composite material: in the presence of a surfactant, the amorphous soft magnetic powder is insulated and coated by hydrolysis of metal organic alcohol salts, and then the low melting point glass phase is evenly dispersed in the organic resin, the resin and the insulated coated amorphous powder are evenly mixed, and then compression molding is performed, and the green body is air annealed at a certain temperature and then nitrogen annealed at 450 to 800°C. The obtained amorphous nanocrystalline soft magnetic composite material has the characteristics of high frequency and low loss, but it introduces more non-ferromagnetic low melting point glass phase, which has an adverse effect on the Bs of the amorphous nanocrystalline soft magnetic composite material; and the insulation coating of the main amorphous soft magnetic powder also has an adverse effect on the magnetic permeability and Bs of the material. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity.
[0007] Another object of the present invention is to provide an amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity prepared by the above method.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity comprises the following preparation steps:
[0010] (1) crushing the iron-based amorphous strip into flat powder with a thickness of 5 to 25 μm and a diameter of 30 to 80 μm to obtain flaky amorphous soft magnetic powder;
[0011] (2) subjecting spherical iron silicon soft magnetic powder having an average particle size of 2 to 20 μm to an insulation coating treatment to obtain an insulation coated modified spherical magnetic powder;
[0012] (3) The flaky amorphous soft magnetic powder obtained in step (1) and the insulating coated modified spherical magnetic powder obtained in step (2) are mixed with a binder resin and then compression molded, firstly annealed and crystallized at a temperature of 450 to 550° C., and then heated to 600 to 900° C. for sintering to obtain a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material.
[0013] Furthermore, the iron-based amorphous strip in step (1) has a composition system of Fe (100-x-y-z) Si x B y M z (x, y, z represent atomic percentages) and an iron-based amorphous strip with a thickness of 5 to 30 μm; wherein 3≤x≤20, 2≤y≤15, 0≤z≤5, and M is at least one metal element selected from Cu, Nb, V, Ti, and Cr.
[0014] Furthermore, the spherical iron silicon soft magnetic powder in step (2) is an atomized spherical iron silicon soft magnetic powder having a silicon atomic percentage of 1% to 12%.
[0015] Furthermore, the iron atomic percentage in the spherical iron silicon soft magnetic powder in step (2) is higher than the iron atomic percentage in the iron-based amorphous strip in step (1).
[0016] Furthermore, the steps of the insulation coating treatment in step (2) are as follows:
[0017] The iron silicon soft magnetic powder is added into the solvent and dispersed evenly, and then the silica sol and the silane coupling agent are added and stirred to mix and react; after the reaction is completed, the powder is spray dried to obtain the insulating coated modified spherical magnetic powder.
[0018] Preferably, the solvent is at least one of ethanol and isopropanol.
[0019] Preferably, the mass ratio of the iron silicon soft magnetic powder, the solvent, the silica sol and the silane coupling agent added is 100:100-400:6-15:2-6.
[0020] Furthermore, the bonding resin in step (3) is epoxy resin, silicone resin or acrylic resin.
[0021] Preferably, the added amount of the bonding resin is 0.5% to 5% of the total mass of the amorphous soft magnetic powder and the insulating coated modified spherical magnetic powder.
[0022] Furthermore, the mass ratio of the amorphous soft magnetic powder and the insulating coated modified spherical magnetic powder mixed in step (3) is 100:1-10.
[0023] A high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material is prepared by the method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention uses a small amount of insulating coated modified spherical iron silicon soft magnetic powder to compound with amorphous soft magnetic powder. On the one hand, it can further improve the saturation magnetic induction intensity of the amorphous nanocrystalline soft magnetic material after annealing and crystallization treatment; on the other hand, by filling the flaky amorphous nanocrystalline soft magnetic powder with small-particle insulating coated modified spherical magnetic powder, it can effectively improve the bonding effect and density of the flaky amorphous nanocrystalline soft magnetic powder, and significantly improve its comprehensive magnetic properties.
[0026] (2) The amorphous nanocrystalline soft magnetic material of the present invention uses flat amorphous soft magnetic powder as the main matrix component. The flaky composite structure formed by composite molding with small-particle insulation-coated modified magnetic powder can effectively reduce magnetocrystalline anisotropy, thereby reducing losses at high frequencies.
[0027] (3) The present invention pre-insulates and coats the iron silicon magnetic powder and / or the iron silicon aluminum magnetic powder with silicon dioxide and silane coupling agent, which can reduce the loss at high frequencies on the one hand, and improve the bonding strength with the adhesive resin on the other hand, effectively improving the bonding effect and uniformity of the flaky amorphous nanocrystalline soft magnetic powder, and improving the comprehensive magnetic properties. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0029] Example 1
[0030] A method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity comprises the following preparation steps:
[0031] (1) The composition system is Fe 80 Si 12 B7Cu1, an iron-based amorphous strip with a thickness of 20 μm is crushed by a jet mill into a flat powder with a thickness of 20 μm and a diameter of 300 mesh, thereby obtaining a scaly amorphous soft magnetic powder.
[0032] (2) The composition system is Fe 91 Si9, aerosolized spherical iron silicon soft magnetic powder with an average particle size of 8 μm was added to the ethanol solvent and dispersed evenly, and then silica sol and silane coupling agent KH-560 were added and stirred and mixed for 1 hour. The mass ratio of iron silicon soft magnetic powder, ethanol solvent, silica sol and silane coupling agent was 100:200:8:3. After the reaction was completed, spray drying was performed to obtain an insulating coated modified spherical magnetic powder.
[0033] (3) The amorphous soft magnetic powder obtained in step (1), the insulating coated modified spherical magnetic powder obtained in step (2) and the epoxy resin binder are mixed in a mass ratio of 100:6:2, and then molded at 80°C and 700 MPa. The temperature is first increased to 500°C at a heating rate of 5°C / min for annealing and crystallization treatment for 90 minutes, and then the temperature is increased to 750°C for heat preservation and sintering treatment for 60 minutes to obtain a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material.
[0034] Example 2
[0035] A method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity comprises the following preparation steps:
[0036] (1) The composition system is Fe 76 Si 14B7Nb2Cu1, an iron-based amorphous strip with a thickness of 15 μm is crushed by a jet mill into a flat powder with a thickness of 15 μm and a diameter of 400 mesh, thereby obtaining a flaky amorphous soft magnetic powder.
[0037] (2) The composition system is Fe 93 Si7, aerosolized spherical iron silicon soft magnetic powder with an average particle size of 8 μm was added to the ethanol solvent and dispersed evenly, and then silica sol and silane coupling agent KH-560 were added and stirred and mixed for 1 hour. The mass ratio of iron silicon soft magnetic powder, ethanol solvent, silica sol and silane coupling agent was 100:200:12:4. After the reaction was completed, spray drying was performed to obtain an insulating coated modified spherical magnetic powder.
[0038] (3) The amorphous soft magnetic powder obtained in step (1), the insulating coated modified spherical magnetic powder obtained in step (2) and the epoxy resin binder are mixed in a mass ratio of 100:5:3, and then molded at 80°C and 600 MPa. The temperature is first increased to 550°C at a heating rate of 5°C / min for annealing and crystallization treatment for 90 minutes, and then the temperature is increased to 800°C and sintered for 60 minutes to obtain a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material.
[0039] Example 3
[0040] A method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity comprises the following preparation steps:
[0041] (1) The composition system is Fe 84 5B 10 Nb1, an iron-based amorphous strip with a thickness of 25 μm is crushed by a jet mill into a flat powder with a thickness of 25 μm and a diameter of 200 meshes, thereby obtaining a flaky amorphous soft magnetic powder.
[0042] (2) The composition system is Fe 88 Si 12 , aerosolized spherical iron silicon soft magnetic powder with an average particle size of 8 μm was added to the ethanol solvent and dispersed evenly, and then silica sol and silane coupling agent KH-560 were added and stirred and mixed for 1 hour, and the mass ratio of iron silicon soft magnetic powder, ethanol solvent, silica sol and silane coupling agent was 100:200:6:2. After the reaction was completed, spray drying was performed to obtain an insulating coated modified spherical magnetic powder.
[0043] (3) The amorphous soft magnetic powder obtained in step (1), the insulating coated modified spherical magnetic powder obtained in step (2) and the epoxy resin binder are mixed in a mass ratio of 100:8:1, and then molded at 80°C and 500 MPa. The temperature is first increased to 450°C at a heating rate of 5°C / min for annealing and crystallization treatment for 90 minutes, and then the temperature is increased to 650°C for heat preservation and sintering treatment for 60 minutes to obtain a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material.
[0044] Comparative Example 1
[0045] A method for preparing an amorphous nanocrystalline soft magnetic material. Compared with Example 1, no insulating coated modified spherical magnetic powder is added, and the rest is the same.
[0046] Comparative Example 2
[0047] A method for preparing an amorphous nanocrystalline soft magnetic material. Compared with Example 2, no insulating coated modified spherical magnetic powder is added, and the rest is the same.
[0048] Comparative Example 3
[0049] A method for preparing an amorphous nanocrystalline soft magnetic material. Compared with Example 3, no insulating coated modified spherical magnetic powder is added, and the rest is the same.
[0050] Comparative Example 4
[0051] A method for preparing an amorphous nanocrystalline soft magnetic material, compared with Example 1, the amorphous soft magnetic powder does not have a flat structure, comprising the following preparation steps:
[0052] (1) The composition system is Fe 80 Si 12 B7Cu1, an iron-based amorphous strip with a thickness of 20 μm was crushed by a jet mill and passed through a 600-mesh sieve to obtain an amorphous soft magnetic powder with an average particle size of 18.3 μm at D90.
[0053] Step (2) and step (3) are the same as in Example 1.
[0054] Comparative Example 5
[0055] A method for preparing an amorphous nanocrystalline soft magnetic material, compared with Example 1, the spherical iron silicon soft magnetic powder is not subjected to insulation coating treatment with silicon dioxide and silane coupling agent, and comprises the following preparation steps:
[0056] Step (1) is the same as in Example 1.
[0057] (2) The amorphous soft magnetic powder obtained in step (1) is Fe 91Si9, aerosolized spherical iron silicon soft magnetic powder with an average particle size of 8μm and epoxy resin binder are mixed in a mass ratio of 100:6:2 and then compression molded at 80℃ and 700MPa. The temperature is first increased to 500℃ at a heating rate of 5℃ / min for annealing and crystallization treatment for 90min, and then the temperature is increased to 750℃ and sintered for 60min to obtain an amorphous nanocrystalline soft magnetic material.
[0058] The saturation magnetic induction intensity Bs and high-frequency loss (FE-2100SA soft magnetic high-frequency BH instrument, 100kHz and 50mT) of the amorphous nanocrystalline soft magnetic materials obtained in the above embodiments and comparative examples were tested, and the results are shown in Table 1 below.
[0059] Table 1
[0060] Test sample / test item Bs(T) <![CDATA[High-frequency loss (mW / cm 3 )]]> Example 1 1.61 295 Example 2 1.48 218 Example 3 1.72 383 Comparative Example 1 1.42 329 Comparative Example 2 1.30 256 Comparative Example 3 1.57 410 Comparative Example 4 1.55 541 Comparative Example 5 1.62 1187
[0061] It can be seen from the comparison results of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1 that the present invention uses a small amount of insulating coated modified spherical iron silicon soft magnetic powder to compound with amorphous soft magnetic powder, which can significantly improve the saturation magnetic induction intensity of the obtained amorphous nanocrystalline soft magnetic material, and can reduce iron loss to a certain extent. It can be seen from the comparison results of Example 1 and Comparative Example 4 that the flaky composite structure obtained by the present invention using flat amorphous soft magnetic powder can effectively reduce the loss under high frequency, and also has a certain effect on the improvement of saturation magnetic induction intensity. It can be seen from the comparison results of Example 1 and Comparative Example 5 that the use of silicon dioxide and silane coupling agent to perform insulation coating treatment on iron silicon soft magnetic powder can significantly reduce the high-frequency loss of the obtained amorphous nanocrystalline soft magnetic material, and has no obvious adverse effect on the saturation magnetic induction intensity of the amorphous nanocrystalline soft magnetic material.
[0062] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing amorphous nanocrystalline soft magnetic material with high saturation magnetic induction intensity, characterized in that: The method comprises the following preparation steps: (1) crushing the iron-based amorphous strip into flat powder with a thickness of 5 to 25 μm and a diameter of 30 to 80 μm to obtain flaky amorphous soft magnetic powder; (2) subjecting spherical iron silicon soft magnetic powder having an average particle size of 2 to 20 μm to an insulation coating treatment to obtain an insulation coated modified spherical magnetic powder; (3) The flaky amorphous soft magnetic powder obtained in step (1) and the insulating coated modified spherical magnetic powder obtained in step (2) are mixed with a binder resin and then compression molded, firstly annealed and crystallized at a temperature of 450 to 550° C., and then heated to 600 to 900° C. for sintering to obtain a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material.
2. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The iron-based amorphous strip in step (1) has a composition system of Fe (100-x-y-z) Si x B y M z , an iron-based amorphous strip with a thickness of 5 to 30 μm; wherein 3≤x≤20, 2≤y≤15, 0≤z≤5, and M is at least one metal element selected from Cu, Nb, V, Ti, and Cr.
3. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The spherical iron silicon soft magnetic powder in step (2) is an atomized spherical iron silicon soft magnetic powder with a silicon atomic percentage of 1% to 12%.
4. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The iron atomic content of the spherical iron silicon soft magnetic powder in step (2) is higher than the iron atomic content of the iron-based amorphous strip in step (1).
5. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The steps of the insulation coating treatment in step (2) are as follows: The iron silicon soft magnetic powder is added into the solvent and dispersed evenly, and then the silica sol and the silane coupling agent are added and stirred to mix and react; after the reaction is completed, the powder is spray dried to obtain the insulating coated modified spherical magnetic powder.
6. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 5, characterized in that: The solvent is at least one of ethanol and isopropanol.
7. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 5, characterized in that: The mass ratio of the iron silicon soft magnetic powder, the solvent, the silica sol and the silane coupling agent added is 100:100-400:6-15:2-6.
8. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The bonding resin in step (3) is epoxy resin, silicone resin or acrylic resin; the amount of the bonding resin added is 0.5% to 5% of the total mass of the amorphous soft magnetic powder and the insulating coated modified spherical magnetic powder.
9. The method for preparing a high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material according to claim 1, characterized in that: The mass ratio of the amorphous soft magnetic powder and the insulating coated modified spherical magnetic powder mixed in step (3) is 100:1-10.
10. A high saturation magnetic induction intensity amorphous nanocrystalline soft magnetic material, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Powder magnetic core and choke
CN101689417A
Compressed powder core, method of manufacturing the compressed powder core, inductor comprising the compressed powder core and electronic-electric device mounted with the inductor
CN107093514A
Soft magnetic composite material and preparation method and application thereof
CN118486519A
Powder-compact magnetic core, and method for manufacturing the same
JP2015005581A
Cited By
Metal soft magnetic composite material, preparation method thereof and magnetic device
CN121545869A
Metallic soft magnetic composite material, method for producing the same, and magnetic device
CN121545869B
High-frequency low-loss iron-nickel soft magnetic powder core and preparation method and application thereof
CN121617766A
A high-frequency low-loss iron-nickel soft magnetic powder core, a preparation method thereof and application thereof
CN121617766B
High-temperature-resistant high-permeability nanocrystalline soft magnetic alloy strip for switch cabinet and preparation method thereof
CN121617769A